Oracle 10g developing media rich applications - Guros, Larry. (Elsevier Digital Press, 2007)
Oracle 10g Developing Media Rich Applications is focused squarely on database administrators and programmers as the foundation of multimedia database applications. With the release of Oracle8 Database in 1997, Oracle became the first commercial database with integrated multimedia technology for application developers. Since that time, Oracle has enhanced and extended these features to include native support for image, audio, video and streaming media storage; indexing, retrieval and processing in the Oracle Database, Application Server; and development tools. Databases are not only words and numbers for accountants, but they also should utilize a full range of media to satisfy customer needs, from race car engineers, to manufacturing processes to security. The full range of audio, video and integration of media into databases is mission critical to these applications. This book details the most recent features in Oracles multimedia technology including those of the Oracle10gR2 Database and the Oracle9i Application Server. The technology covered includes: object relational media storage and services within the database, middle tier application development interfaces, wireless delivery mechanisms, and Java-based tools. * Gives broad coverage to integration of multimedia features such as audio and instrumentation video, from race cars to analyze performance, to voice and picture recognition for security data bases. As well as full multimedia for presentations * Includes field tested examples in enterprise environments * Provides coverage in a thorough and clear fashion developed in a London University Professional Course.